Preliminary evaluation of complex decongestive therapy in the treatment of upper limb lymphedema after breast cancer - Van, Mai Thi Hong; Thuy, Nguyen Thi Thu; Quang, Cai Viet; Hai, Dang Thi Thanh; Phuong, Chau Uyen (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Background: Secondary upper limb lymphedema is a common complication after breast cancer treatment. Among the treatment methods, conservative treatment with complex decongestive therapy brings positive results to patients and it is non - invasive. Methods: Cross - sectional description of 7 cases diagnosed with lymphedema after breast cancer and treated with complex decongestive therapy. Assessment was based on limb circumference with 4 different measuring positions and Quick - Disabilities of the Arm, Shoulder and Hand (Q-DASH). Results: The mean age was 58.4 (42 - 73), there was 1 patient in stage I, 5 patients were in stage II and 1 patient was in stage III. After 1 month of treatment, all patient’s hand circumferences were decreased, of which 1 patient was returned to normal hand circumference. All 7 patients were decreased Q-DASH scores. Conclusion: This technique can be widely applied to other patients with upper limb lymphedema after breast cancer. This study needs to be performed with a larger sample size to confirm effectiveness.